Where do we go from here? – Opportunities and barriers to the career development of trial managers: a survey of UK-based trial management professionals - Eleanor Mitchell; Kirsteen Goodman; Suzanne Hartley; Helen Hickey; Alison M. McDonald; Helen M. Meadows; Shelley Rhodes; Jodi Taylor; Natalie Wakefield; Barbara Farrell; on behalf of the UK Trial Managers’ Network Executive Group (Trials, 2020)
Abstract Background Clinical trials commonly have a dedicated trial manager and effective trial management is essential to the successful delivery of high-quality trials. Trial managers have diverse experience and currently there is no standardised structured career pathway. The UK Trial Managers’ Network (UKTMN) surveyed its members to understand what is important to them with respect to career development since this would be important in the development of any initiative intended to develop a skilled workforce. Methods We conducted an online survey of UKTMN members, who are trial management professionals, working on academic-led trials in the UK. Members were asked what they perceive as opportunities and barriers to career development. Two reminders were sent to facilitate completion of the survey, and responders were offered the opportunity to enter a prize draw for waived fees at the UKTMN annual meeting. Data were analysed descriptively by using Stata (version 15.1), and free-text responses were reviewed for themes. Results The survey was sent to 819 UKTMN members; 433 responses were received, although 13 were from non-UKTMN members; thus 420 respondents' data were included in analyses. Respondents were representative of UKTMN membership; however, more responses were received by trial managers based in registered clinical trials units (CTUs). The top three opportunities for career development were (i) training, (ii) helping design trials and (iii) undertaking relevant qualifications. The top three barriers were (i) funding, (ii) few opportunities to get involved in development activities aside from managing a trial and (iii) unclear organisational career pathway. Almost all respondents (401/420, 95.4%) considered career development either very or quite important. Although all respondents had a day-to-day role in managing trials, there was huge disparity between job titles. Conclusion Career development is important to trial managers yet there is a lack of a structured pathway. The enablers and disablers to career development for trial managers should be clearly considered by the clinical trial community and, in particular, employers, sponsors and funders in order to develop a highly skilled workforce of trial managers, who are key to the delivery of trials.